Appropriateness of antibiotic prescription among hospitalized patients with urinary tract infection in Jordan - Anan Jarab,, Treq Lewis Mukattash, Buthaina Nusairat, Maher Khdour (Journal of Applied Pharmaceutical Science, 2023)
Lack of adherence to recent antibiotic prescription guidelines leads to antibiotic resistance which causes treatment failure and the development of disease complications in patients with urinary tract infection (UTI). The study aim was to evaluate patterns and appropriateness of antibiotic selection among hospitalized patients with UTI. The computerized medical records of the hospitalized patients in the Urology Department at King Abdullah University Hospital were used for data collection. The American Urological Association and the Infectious Disease Society of America guidelines of UTI management were used as references to determine the appropriateness of antibiotic prescription in different cases of UTI. Statistical analysis using Excel program, 2015 version, was used for data analysis. A total of 168 intravenous (IV) antibiotic prescriptions were prescribed for 148 hospitalized UTI patients. Imipenem/cilastatin was the most common prescribed antibiotic and used in 66.7% of complicated cystitis and 57.1% of complicated pyelonephritis cases, while 75% of the participants received ceftriaxone as the most common prescribed antibiotic in uncomplicated pyelonephritis. Imipenem/cilastatin and ceftriaxone were equally the most prescribed antibiotics among patients with prostatitis. The choice of antibiotics was inappropriate in 32.43% of the studied cases. The most common inappropriate antibiotic choice was prescribing IV ceftriaxone and IV imipenem/ cilastatin in cases with uncomplicated pyelonephritis and complicated cystitis and prostatitis. Lack of adherence to antibiotic selection guidelines sheds light on the necessity to improve antibiotics prescription practice and avoid the inappropriate antibiotic selection and hence antibiotic resistance among patients with UTI.
Keywords: Antibiotics, UTI, prescription patterns, antimicrobial resistance, hospitalized patients, Jordan